Life-cycle contract as an innovative business model for high-tech medical organizations - Igor Ilin; Anastasia Levina; Konstantin Frolov; Alexandra Borremans; Alyona Ershova; Andrea Tick; Mariia Averina (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The active digitalization of the healthcare system has given impetus to the emergence of a new type of enterprise-high-tech medical organizations (HMO). Their main distinguishing feature is the use of innovative high-tech medical equipment. However, the high cost of this equipment has become a factor slowing down the development of such organizations. This paper considers the life-cycle contract (LCC) as a special form of interaction between stakeholders and investments throughout the life cycles of equipment. Moreover, to provide technological support, continuous acquisition and life-cycle support (CALS) technologies, which are based on the same principles of working with the life cycle as LCC, are proposed. This question turned out to be a significant research gap, which was not sufficiently reflected in the available world studies. Thus, the aim of the current study is to describe the features of the use of LCC for HMO using CALS technologies and the impact of the life cycle of high-tech medical equipment on LCC, as well as to present the innovative component of the proposed model. Based on the analysis of the literature and the best world practices, the authors propose a visualization of the interaction of all stakeholders within the LCC for HMO. Such a decision is extremely relevant for developing organizations, public authorities and investors around the world.
Keywords: 650; CALS in health care; high-tech medicine; innovations in health care; life-cycle contract; life-cycle contract in health care; medical equipment